Functional Properties of Human Primary Motor Cortex Gamma Oscillations - Muthukumaraswamy, Suresh D. (Journal of neurophysiology, 2010)
Gamma oscillations in human primary motor cortex (M1) have been described in human electrocorticographic and noninvasive magnetoencephalographic (MEG)/electroencephalographic recordings, yet their functional significance within the sensorimotor system remains unknown. In a set of four MEG experiments described here a number of properties of these oscillations are elucidated. First, gamma oscillations were reliably localized by MEG in M1 and reached peak amplitude 137 ms after electromyographic onset and were not affected by whether movements were cued or self-paced. Gamma oscillations were found to be stronger for larger movements but were absent during the sustained part of isometric movements, with no finger movement or muscle shortening. During repetitive movement sequences gamma oscillations were greater for the first movement of a sequence. Finally, gamma oscillations were absent during passive shortening of the finger compared with active contractions sharing similar kinematic properties demonstrating that M1 oscillations are not simply related to somatosensory feedback. This combined pattern of results is consistent with gamma oscillations playing a role in a relatively late stage of motor control, encoding information related to limb movement rather than to muscle contraction.